Lactic Acidosis in a Congenital Bone Marrow Failure Syndrome - Fatima Farid Mir; Anjan Madasu; Hani Humad; Asim Noor Rana (Dubai Medical Journal, 2021)
Fifteen-month-old male child, known to have a congenital bone marrow failure syndrome, presented in a state of shock with severe lactic acidosis following a brief episode of vomiting. Hospital stay was complicated by recurrent bouts of metabolic acidosis and progressive hepatic failure. Blood mitochondrial DNA sequencing revealed a large heteroplasmic 4,977 bp mitochondrial deletion (approximately 40% of all mitochondrial copies) suggestive of Pearson marrow-pancreas syndrome. By virtue of natural disease course, within a month of admission child succumbed to end-stage liver failure with multi-organ failure and died.